Direct Determination of Activities for Microorganisms of Chesapeake Bay Populations - Tabor, Paul S. (1984)
We used three methods in determination of the metabolically active individual microorganisms for Chesapeake Bay surface and near-bottom populations over a period of a year. Synthetically active bacteria were recognized as enlarged cells in samples amended with nalidixic acid and yeast extract and incubated for 6 h. Microorganisms with active electron transport systems were identified by the reduction of a tetrazolium salt electron acceptor. Microorganisms active in uptake of amino acids, thymidine, and acetate were determined by microautoradiography. In conjunction with enumeration of active organisms, a total direct count was made for each sample preparation by epifluorescence microscopy. For the majority of samples, numbers of amino acid uptake-active organisms were greater than numbers of organisms determined to be active by other direct measurements. Within a sample, the numbers of uptake-active organisms (amino acids or thymidine) and electron transport system-active organisms were significantly different for 68% of the samples. Numbers of synthetically active bacteria were generally less than numbers determined by the other direct activity measurements. The distribution of total counts in the 11 samplings showed a seasonal pattern, with significant dependence on in situ water temperature, increasing from March to September and then decreasing through February. Synthetically active bacteria and amino acid uptake-active organisms showed a significant dependence on in situ temperature, independent of the function of temperature on total counts. Numbers of active organisms determined by at least one of the methods used exceeded 25% of the total population of all samplings, and from June through September, >85% of the total population was found to be active by at least one direct activity measurement. Thus, active rather than dormant organisms compose a major portion of the microbial population in this region of Chesapeake Bay.